Disrupting the Interaction of nNOS with CAPON Prevents the Reinstatement of Morphine Conditioned Place Preference. (23rd July 2021) - Kou, Xiaolin; Xian, Jiayun; Huang, Zhenquan; Tao, Yan; Lin, Yuhui; Qin, Cheng; Wu, Haiyin; Chang, Lei; Luo, Chunxia; Zhu, Dongya
Abstract: Drug abuse is a dramatic challenge for the whole society because of high relapse rate. Environmental cues are crucial for the preference memory of drug abuse. Extinction therapy has been developed to inhibit the motivational effect of drug cues to prevent the reinstatement of morphine abuse. However, extinction therapy alone only forms a new kind of unstable inhibitory memory. We found that morphine conditioned place preference (CPP) extinction training increased the association of nitric oxide synthase (nNOS) with its carboxy-terminal PDZ ligand (CAPON) in the dorsal hippocampus (dHPC) significantly and blocking the morphine-induced nNOS–CAPON association using Tat-CAPON-12C during and after extinction training reversed morphine-induced hippocampal neuroplasticity defect and prevented the reinstatement and spontaneous recovery of morphine CPP. Moreover, in the hippocampal selective ERK2 knock-out or nNOS knockout mice, the effect of Tat-CAPON-12C on the reinstatement of morphine CPP and hippocampal neuroplasticity disappeared, suggesting ERK2 is necessary for the effects of Tat-CAPON-12C. Together, our findings suggest that nNOS–CAPON interaction in the dHPC may affect the consolidation of morphine CPP extinction and dissociating nNOS–CAPON prevents the reinstatement and spontaneous recovery of morphine CPP, possibly through ERK2-mediated neuroplasticity and extinction memory consolidation, offering a new target to prevent the reinstatement of drug abuse.